Impact of mechanized clam dredging on the discarded megabenthic fauna on the Catalan coast (NW Mediterranean). (2nd May 2021) - Baeta, Marc; Rubio, Claudia; Breton, Françoise
Abstract: There is an important small-scale fishery using mechanized dredges and targeting clams (mainly wedge clam Donax trunculus and striped venus clam Chamelea gallina ) along the Catalan coast (NW Mediterranean Sea). This study evaluated for the first time the discards and impact of mechanized clam dredging on the Catalan coast. To this end, three surveys were performed on board standard clam vessels (September and November 2016 and January 2017). Surveys were conducted in the three main clam fishing areas (Rosas Bay, South Barcelona and Ebro Delta). The composition of discards and the impact caused to discarded species was assessed using a three-level scale (undamaged; minor or partial damage; and lethal damage). Our study revealed that a large proportion of the catch (between 67–82% weight) is discarded. Even though about 63% of the discarded species were undamaged, 11% showed minor or partial damage and 26% lethal damage. Infaunal and epifaunal species with soft-body or fragile shells were the most impacted by the fishing activity (e.g. the sea urchin Echinocardium mediterraneum (~89%) and the bivalve Ensis minor (~74%)). Our results showed different levels of impact by target species and fishing area.